Mistress of The House, Mistress of Heaven: Women in Ancient Egypt - Catharine H. Roehrig; Glenn E. Markoe; Anne K. Capel; Besty M. Bryan; Janet H. Johnson (USA Hudson Hills Press, 1997)
Masterpieces of Egyptian art dating from 3000 to 300 B.C. have been brought together from great American museum and private collections to illuminate the role of women in ancient Egyptian society. This magnificent volume explores the full spectrum of women's lives and pursuits through three millennia of history. The dazzling centerpiece of Mistress of the House, Mistress of Heaven is devoted to more than one hundred objects assembled for the accompanying exhibition
organized by the Cincinnati Art Museum and shown also at the Brooklyn Museum. The exhibition was curated, and this volume edited, by Glenn Markoe, Curator of Classical and Near Eastern Art at Cincinnati, and Anne K. Capel, Guest Curator. Here are prime examples of stone and wood sculpture; wall painting; statuettes in bronze, terracotta, and faience; a mummy case; a painted and gilded wood coffin; jewelry in gold, stone and faience; and vessels and utensils in bronze
glass, and stone. Organized into sections devoted to Public and Private Lives, Female Royalty, Goddesses, and Afterlife, most are reproduced in full color, and all are accompanied by individual essays. The reader's understanding is further enriched by the inclusion of a chronology, map, bibliography, and index
Woman's work : some occupations of nonroyal women as depicted in ancient Egyptian art / Catharine H. Roehrig -- In women good and bad fortune are on earth : status and roles of women in Egyptian culture / Betsy M. Bryan -- The legal status of women in ancient Egypt / Janet H. Johnson
Exhibition catalog
"Published in conjunction with the exhibition organized by the Cincinnati Art Museum, Cincinnati, Ohio, October 20, 1996 through January 5, 1997, and also appearing at The Brooklyn Museum (February 21 through May 18, 1997)"--T.p. verso
Keywords: Women in art -- Exhibitions; Art, Egyptian -- Exhibitions; Art, Ancient -- Egypt -- Exhibitions; General